Vascular Anomaly Syndromes in the ISSVA Classification System: Imaging Findings and Role of Interventional Radiology in Management - Wang, Mindy X; Kamel, Serageldin; Elsayes, Khaled M; Guillerman, R Paul; Habiba, Ahmed; Heng, Lauren; Revzin, Margarita; Mellnick, Vincent; Iacobas, Ionela; Chau, Alex (Radiographics, 2022)
Vascular anomalies encompass a spectrum of tumors and malformations that can cause significant morbidity and mortality in children and adults. Use of the International Society for the Study of Vascular Anomalies (ISSVA) classification system is strongly recommended for consistency. Vascular anomalies can occur in isolation or in association with clinical syndromes that involve complex multifocal lesions affecting different organ systems. Thus, it is critical to be familiar with the differences and similarities among vascular anomalies to guide selection of the appropriate imaging studies and possible interventions. Syndromes associated with simple vascular malformations include hereditary hemorrhagic telangiectasia, blue rubber bleb nevus syndrome, Gorham-Stout disease, and primary lymphedema. Syndromes categorized as vascular malformations associated with other anomalies include Klippel-Trenaunay-Weber syndrome, Parkes Weber syndrome, Servelle-Martorell syndrome, Maffucci syndrome, macrocephaly-capillary malformation, CLOVES (congenital lipomatous overgrowth, vascular malformations, epidermal nevi, and scoliosis, skeletal, and spinal anomalies) syndrome, Proteus syndrome, Bannayan-Riley-Ruvalcaba syndrome, and CLAPO (capillary malformations of the lower lip, lymphatic malformations of the face and neck, asymmetry of the face and limbs, and partial or generalized overgrowth) syndrome. With PHACES (posterior fossa malformations, hemangiomas, arterial anomalies, cardiac defects and/or coarctation of the aorta, eye abnormalities, and sternal clefting or supraumbilical raphe) syndrome, infantile hemangiomas associated with other lesions occur. Diagnostic and interventional radiologists have important roles in diagnosing these conditions and administering image-guided therapies-embolization and sclerotherapy, and different ablation procedures in particular. The key imaging features of vascular anomaly syndromes based on the 2018 ISSVA classification system and the role of interventional radiology in the management of these syndromes are reviewed. Online supplemental material is available for this article. ©RSNA, 2022.Vascular anomalies encompass a spectrum of tumors and malformations that can cause significant morbidity and mortality in children and adults. Use of the International Society for the Study of Vascular Anomalies (ISSVA) classification system is strongly recommended for consistency. Vascular anomalies can occur in isolation or in association with clinical syndromes that involve complex multifocal lesions affecting different organ systems. Thus, it is critical to be familiar with the differences and similarities among vascular anomalies to guide selection of the appropriate imaging studies and possible interventions. Syndromes associated with simple vascular malformations include hereditary hemorrhagic telangiectasia, blue rubber bleb nevus syndrome, Gorham-Stout disease, and primary lymphedema. Syndromes categorized as vascular malformations associated with other anomalies include Klippel-Trenaunay-Weber syndrome, Parkes Weber syndrome, Servelle-Martorell syndrome, Maffucci syndrome, macrocephaly-capillary malformation, CLOVES (congenital lipomatous overgrowth, vascular malformations, epidermal nevi, and scoliosis, skeletal, and spinal anomalies) syndrome, Proteus syndrome, Bannayan-Riley-Ruvalcaba syndrome, and CLAPO (capillary malformations of the lower lip, lymphatic malformations of the face and neck, asymmetry of the face and limbs, and partial or generalized overgrowth) syndrome. With PHACES (posterior fossa malformations, hemangiomas, arterial anomalies, cardiac defects and/or coarctation of the aorta, eye abnormalities, and sternal clefting or supraumbilical raphe) syndrome, infantile hemangiomas associated with other lesions occur. Diagnostic and interventional radiologists have important roles in diagnosing these conditions and administering image-guided therapies-embolization and sclerotherapy, and different ablation procedures in particular. The key imaging features of vascular anomaly syndromes based on the 2018 ISSVA classification system and the role of interventional radiology in the management of these syndromes are reviewed. Online supplemental material is available for this article. ©RSNA, 2022.